Sounds of origin in heavy metal music - Karjalainen, Toni-Matti (Cambridge Scholars Publishing, 2018)
"This book originates from the 2017 edition of the multidisciplinary Modern Heavy Metal Conference, organised in Helsinki, Finland. This collection of seven scholarly essays explores local scenes and identities within heavy metal music from multiple angles, covering a variety of different countries and metal sub-genres from Finland to Indonesia, and from black metal to metalcore. The essays here lay various theoretical perspectives and incorporate vivid examples with metal bands and scenes from all over the world. By exploring themes and discourses that are central to both research and practice, this book appeals to a versatile global readership. It serves the wide academic communities of metal music and popular music studies as well as of many other streams within cultural and social studies. This book also provides the large and active global community of heavy metal fans with a highly interesting package of genre information and country perspectives"--Back cover